Assessment through interviewing - Shouksmith, George (Oxford, England ; New York : Pergamon Press, 1978)
The book discusses the use and practice of interviewing in selection and other assessment situations. It also includes extended materials on planning for the interview and on the conduct of the interview, aimed at making its coverage of the basic concerns more comprehensive.
Includes index.
Includes bibliographical references: p. 143-145.
occ 16/01/2019
Loans
Keywords: Interviewing